Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Select the correct answer.

The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the [tex]y[/tex]-variable, and what is the solution for this system?

[tex]\[
\begin{array}{l}
x + 3y = 42 \\
2x - y = 14
\end{array}
\][/tex]

A. Multiply the second equation by -3. The solution is [tex]x=12, y=9[/tex].

B. Multiply the second equation by -2. The solution is [tex]x=12, y=10[/tex].

C. Multiply the second equation by 2. The solution is [tex]x=15, y=9[/tex].

D. Multiply the second equation by 3. The solution is [tex]x=12, y=10[/tex].


Sagot :

To solve the given system of equations and eliminate the [tex]\( y \)[/tex]-variable, we can use the elimination method. Let's follow a step-by-step approach to solve this system of equations:

Given system of equations:
[tex]\[ \begin{array}{l} x + 3y = 42 \quad \text{(Equation 1)} \\ 2x - y = 14 \quad \text{(Equation 2)} \end{array} \][/tex]

1. Identify a common coefficient for [tex]\( y \)[/tex]:

In Equation 1, the coefficient of [tex]\( y \)[/tex] is 3.

In Equation 2, the coefficient of [tex]\( y \)[/tex] is -1.

To eliminate [tex]\( y \)[/tex], we need to make the coefficients of [tex]\( y \)[/tex] in both equations equal in magnitude but opposite in sign.

2. Multiply Equation 2 by the appropriate number to match the coefficient of [tex]\( y \)[/tex] in Equation 1:

Since the coefficient of [tex]\( y \)[/tex] in Equation 1 is 3, we multiply Equation 2 by 3:
[tex]\[ 3 \cdot (2x - y) = 3 \cdot 14 \][/tex]
[tex]\[ 6x - 3y = 42 \][/tex]

3. Rewrite the system with the new Equation 2:
[tex]\[ \begin{array}{l} x + 3y = 42 \quad \text{(Equation 1)} \\ 6x - 3y = 42 \quad \text{(New Equation 2)} \end{array} \][/tex]

4. Add the two equations to eliminate [tex]\( y \)[/tex]:
[tex]\[ (x + 3y) + (6x - 3y) = 42 + 42 \][/tex]
[tex]\[ x + 6x + 3y - 3y = 84 \][/tex]
[tex]\[ 7x = 84 \][/tex]

5. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{84}{7} \][/tex]
[tex]\[ x = 12 \][/tex]

6. Substitute [tex]\( x = 12 \)[/tex] back into Equation 1 (or Equation 2) to solve for [tex]\( y \)[/tex]:
Using Equation 1:
[tex]\[ 12 + 3y = 42 \][/tex]
[tex]\[ 3y = 42 - 12 \][/tex]
[tex]\[ 3y = 30 \][/tex]
[tex]\[ y = \frac{30}{3} \][/tex]
[tex]\[ y = 10 \][/tex]

Therefore, the solution to the system is [tex]\( x = 12 \)[/tex] and [tex]\( y = 10 \)[/tex].

Answer D is correct: Multiply the second equation by 3. The solution is [tex]\( x = 12 \)[/tex], [tex]\( y = 10 \)[/tex].